THE ROLE OF PUBLIC ADMINISTRATION IN ECONOMIC DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2023)
Public administration plays a crucial role in fostering economic development by creating and implementing policies that promote growth, stability, and prosperity within a country. As the backbone of government operations, public administration is responsible for ensuring that economic policies are effectively translated into actionable programs and services that benefit society. By managing resources, coordinating government activities, and facilitating public-private partnerships, public administrators help build an environment conducive to sustainable economic development. One of the primary ways public administration contributes to economic development is through the formulation and enforcement of policies aimed at improving infrastructure, education, healthcare, and the business climate. A well-structured public administration system ensures that these policies are efficiently implemented, with resources allocated in a way that maximizes impact. For instance, investing in infrastructure, such as transportation networks and energy systems, creates a foundation for industries to thrive and enhances overall productivity. Additionally, public administration plays a vital role in creating regulatory frameworks that encourage investment, entrepreneurship, and innovation. By establishing fair and transparent legal systems, ensuring the protection of property rights, and fostering a stable political environment, public administration can attract both domestic and foreign investments, thus stimulating economic growth.